EFFECT OF TAMOXIFEN ON PLASMA LIPID PROFILE IN PATIENTS OF BREAST CANCER - Bhunisha Mahadev; Haider, Ghulam; Shaikh, Zoya; Kumar, Pavan; Memon, Paras; Rahul, Raja; Parkash, Jai; Nouman, Maryum; Khalil Mehar; Shaikh, Mehwish Roshan (Journal of Ayub Medical College Abbottabad, 2023)
Background: To evaluate the effect of Tamoxifen on plasma lipid profile in breast cancer patients presenting at tertiary care hospital. Methods: It was a longitudinal study conducted at the department of oncology of Jinnah Postgraduate Medical Center from December 2018 to November 2019. Eighty-eight females of age 26-66 years diagnosed with breast cancer were included in the study using non-probability consecutive sampling technique. Detailed gynaecological and clinical investigations and detailed history were taken. The blood samples of all the patients were collected and plasma lipid profile was measured before initiation of Tamoxifen treatment and three- and six-months post treatment at clinical laboratory. The plasma lipid profile includes the measurement of Total cholesterol (mg/dl), Triglyceride(mg/dl), High density Lipoprotein (mg/dl) & Low-density Lipoprotein (mg/dl). SPSS version 23 was used to analyse data. Results: After treatment there was significant reduction in serum cholesterol & Low-density Lipoprotein level by 20.54 mg/dl & 16.46 mg/dl at 3 months (p<0.05), moreover there was significant increase in Triglyceride by 22.14 at 3 months (p<0.05). No significant difference was observed in High density lipoprotein level at 3-months after using Tamoxifen. At 6 months there was significant reduction in serum cholesterol & Low-density lipoprotein by 32.29mg/dl and 24.11 mg/dl at 6 months (p<0.05), moreover there was significant increase in Triglyceride level by 42.19 mg/dl at 6 months (p<0.05). No significant difference was observed in High density lipoprotein level at 6 months after using Tamoxifen. Conclusion: Total cholesterol and Low-density Lipoprotein levels showed significant reduction over the period of six months from the baseline with the use of Tamoxifen. Hence Tamoxifen should be considered to have an added advantage on lipid metabolism and therefore, can reduce the risk of cardiovascular events.